Development of Instagram Filters in Interactive E-Books Mathematics Learning Build a Flat Side Space - Annisa Gita Cahyani; Setyadi, Danang (Universitas Islam Ahmad Dahlan (UIAD), 2023)
Abstract In facing the challenges of the 21st century, mathematics must be studied well in the digital world, so that digital learning media can be said to be important in the learning process. This study aims to develop an interactive E-book channeling medium on flat-sided space building materials. The subjects in this study were class VIII students of SMP Negeri 1 Salatiga. This research is Research and Development research. The development model in this study is ADDIE (Analyz, Design, Development, Implementation, and Evaluation). Data collection techniques from this interactive E-book development research are observations, tests, and questionnaires for the assessment of validation, practicality, and effectiveness of interactive E-book media to build a flat side space. The final results of the media validity data analysis are 96.67%, the validity of the material is 86.67%, the practicality is 100%, and the effectiveness of having a significant value of 0.000 or less than 0.05 can be stated that the interactive E-book learning media is